2014
DOI: 10.1186/1479-5876-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Decreased oxygen extraction during cardiopulmonary exercise test in patients with chronic fatigue syndrome

Abstract: BackgroundThe insufficient metabolic adaptation to exercise in Chronic Fatigue Syndrome (CFS) is still being debated and poorly understood.MethodsWe analysed the cardiopulmonary exercise tests of CFS patients, idiopathic chronic fatigue (CFI) patients and healthy visitors. Continuous non-invasive measurement of the cardiac output by Nexfin® (BMEYE B.V. Amsterdam, the Netherlands) was added to the cardiopulmonary exercise tests. The peak oxygen extraction by muscle cells and the increase of cardiac output relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…Our data, suggesting that ME/CFS is associated with impaired efficiency of energy metabolism combined with lactate overproduction, may explain why many ME/CFS patients reach anaerobic threshold at a low workload (9)(10)(11). This is supported by an individual patient report (35) and our own observations of patients with severe ME/CFS that had lactate levels elevated to more than 8 mM from just standing upright for 10 minutes.…”
Section: Discussionsupporting
confidence: 82%
“…Our data, suggesting that ME/CFS is associated with impaired efficiency of energy metabolism combined with lactate overproduction, may explain why many ME/CFS patients reach anaerobic threshold at a low workload (9)(10)(11). This is supported by an individual patient report (35) and our own observations of patients with severe ME/CFS that had lactate levels elevated to more than 8 mM from just standing upright for 10 minutes.…”
Section: Discussionsupporting
confidence: 82%
“…In comparison to values reported in other ME/CFS populations, our study participants had similar steps per day [21], and %peak VO 2 values [22,27,30]. The reported median or mean physical functioning scale of the SF-36 questionnaire vary widely between studies ranging between 17 and 59% [13][14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 67%
“…Cardiopulmonary exercise testing (CPET): patients underwent a symptom-limited exercise test on a cycle ergometer (Excalibur, Lode, Groningen, The Netherlands) according to a previously described protocol [22]. A RAMP workload protocol was used varying between 10-30 Watt/min increases, depending on sex, age and expected exercise intolerance.…”
Section: Study Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The gold standard for measuring the severity of physical activity intolerance is cardiopulmonary exercise testing (CPET). Multiple studies have shown that peak oxygen consumption is reduced in the majority of ME/CFS patients (De Becker et al, 2000;Fulcher & White, 2000;Hodges et al, 2018;Jammes et al, 2005;Keller et al, 2014;Sargent et al, 2002;Sisto et al, 1996;Snell et al, 2013;Vanness et al, 2007;Vermeulen et al, 2010;Vermeulen & Vermeulen van Eck, 2014;Wallman et al, 2004). However, studies have also shown that a single CPET may show in ME/CFS patients that peak VO 2 values can be similar to or only slightly lower than those of healthy sedentary controls.…”
Section: Introductionmentioning
confidence: 99%